Aktivitas Antibakteri In Vitro dan Sitotoksisitas Pendahuluan dari Kombucha Kunyit Putih (Curcuma zedoaria) - Siregar, Tobias Hezkel; Muttaqin, Mafrikhul; Syaefudin (Innovation Centre for Tropical Sciences, 2025)
White turmeric (Curcuma zedoaria) contains bioactive compounds with antibacterial and cytotoxic potential; however, the quantity of these compounds and their biological activity remain relatively low. Fermentation can enhance these properties by promoting microbial bioconversion. This study evaluated the total flavonoid content as well as antibacterial and cytotoxic activities of C. zedoaria rhizomes fermented using a Symbiotic Culture of Bacteria and Yeast (SCOBY). Antibacterial activity was evaluated against Escherichia coli and Staphylococcus aureus using the disk diffusion method, while cytotoxic activity was analyzed using the Brine Shrimp Lethality Test (BSLT). The results showed that fermentation increased the total flavonoid content by 64% and substantially improved antibacterial performance, producing inhibition zones of 13.7±0.7 mm for E. coli and 12.8±0.4 mm for S. aureus, more than double those of the non-fermented white turmeric. Cytotoxic activity also increased, as indicated by a lower LC50 value (145.3 µg/ml) compared to the non-fermented white turmeric (1,381.8 µg/ml). Overall, the findings demonstrate that fermentation significantly enhances the antibacterial and cytotoxic activities of white turmeric. Keywords: bioactivity enhancement, fermentation, functional beverage, SCOBY, white turmeric